Integration of CLIL Fundamentals and Principles in the Initial Cycle at San Bonifacio de las Lanzas School - Correa-Guzmán, Jose Miguel (My University, 2017)
This dissertation analyzes the integration of CLIL fundamentals and principles in the Initial Cycle at San Bonifacio de las Lanzas School in Ibagué, Tolima. This study provides a better understanding of effective bilingual education at preschool and primary school level. Even though, CLIL is not one of the mainstream approaches in the National Bilingual Programme, its fundamentals and principles are crucial for understanding pedagogical aspects of bilingual education in this research project. This study was carried taking into account theoretical aspects from the 4 Cs Framework described by Coyle (2006), who explains the integration of language and learning, in terms of content, communication, cognition, and culture. Other important theoretical aspects were taken from the core features of CLIL proposed by Mehisto, et al. (2008), who presented six different elements that are essential in CLIL: multiple foci, safe and enriching learning environment, authenticity, active learning, scaffolding and co-operation. The results of this research study, obtained though the triangulation of data from surveys and interviews, and the analysis of two lesson plans, let us describe the CLIL fundamentals and principles identified by the teachers, their evidence in teaching practices, and the participants’ reactions and opinions towards bilingual education. These findings offer enough information about the CLIL fundamentals and principles that are immersed in the teachers’ lessons plans and teaching practices. Thus, the teachers had some common ideas in relation to the way they develop the CLIL 4 Cs and core features in their classes; additionally, the research participants recognizes some benefits and challenges of bilingual education.
Keywords: CLIL; Content and Language Integrated Learning; bilingual education; 4 Cs framework; CLIL core features; educación bilingüe; Máster Universitario en Educación Bilingüe